Parental feeding pada ibu bekerja yang memiliki anak usia dini di Makassar - Rohma Rifani; Suryanto Suryanto; Dewi Retno Suminar (Seminar Nasional LP2M UNM, 2019)
Many parents feed their children just to fulfill their responsibilities and so that their children feel full. This condition causes nutritional intake not to meet a balanced diet. This study wanted to find out the purpose of parental feeding for the working mothers for their children at an early age in Makassar. This study uses the construct realism approach by referring to a grounded theory approach. Retrieving data through three stages; first, surveys with multi-response open questions. The second stage is through focus group discussion and the third stage through depth interviews. Criteria for the respondents, namely working mothers, having children at an early age, living in Makassar. The respondents in the study filled out a questionnaire (N = 348 with 759 responses). Data analysis was carried out by using the help of the envivo 1 program, peer review and expert review. The results of the research data analysis showed that the purpose of parental feeding consisted of six dimensions; (1) maintaining health, (2) meeting nutritional needs, (3) physical growth, (4) mental growth / intelligence, (5) getting used to healthy eating, and (6) building emotional closeness. Conclusion; feeding children aims to fulfill basic (physical) needs; only a few realize that feeding can be used as a means to build healthy eating patterns and emotional closeness